PROSES PENGAMBILAN KEPUTUSAN DENGAN MODEL ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENENTUAN BIAYA DELIVERY YANG PALING OPTIMAL PADA GOJEK INDONESIA - Sidik, Aditya Ihsan; Choirunnissa, Dina; Lukita, Chandra; Pranata, Sudadi (Fakultas Ekonomi dan Bisnis, 2023)
Making effective decisions in determining optimal delivery costs is an important challenge in the delivery service industry as faced by Gojek Indonesia. The Analytical Hierarchy Process (AHP) model is a decision-making method that has been proven effective in dealing with complexity and uncertainty in multi-criteria decision-making processes. The data source for this research was obtained through a questionnaire that was distributed online by Gofood users in Indonesia with a total sample of 100. The purpose of this study was to apply the AHP model in determining the most optimal delivery costs to increase operational efficiency and customer satisfaction for Gojek Indonesia. In this case, it has 6 criteria, namely delivery distance, package size weight, delivery time, mode of transportation delivery route, special requirements and 18 alternatives. The results of this study are that JP 3, BU 3, WP 3, MT 3, RP 3, PK 3 ranks first with a priority weight of 0.338732583, which means questions from JP 3, BU 3, WP 3, MT 3, RP 3, PK 3 is the most important criterion for determining optimal costs for Gojek Indonesia.Key words: Food Delivery Application, Optimum Cost, Analytical Hierarchy Process